Series-Spatial Transcriptome Profiling of Leafy Head Reveals the Key Transition Leaves for Head Formation in Chinese Cabbage - Guo, Xinlei; Liang, Jianli; Lin, Runmao; Zhang, Lupeng; Wu, Jian; Wang, Xiaowu (Frontiers in Plant Science, 2022)
Chinese cabbage is an important leaf heading vegetable crop. At the heading stage, its leaves across inner to outer show significant morphological differentiation. However, the genetic control of this complex leaf morphological differentiation remains unclear. Here, we reported the transcriptome profiling of Chinese cabbage plant at the heading stage using 24 spatially dissected tissues representing different regions of the inner to outer leaves. Genome-wide transcriptome analysis clearly separated the inner leaf tissues from the outer leaf tissues. In particular, we identified the key transition leaf by the spatial expression analysis of key genes for leaf development and sugar metabolism. We observed that the key transition leaves were the first inwardly curved ones. Surprisingly, most of the heading candidate genes identified by domestication selection analysis obviously showed a corresponding expression transition, supporting that key transition leaves are related to leafy head formation. The key transition leaves were controlled by a complex signal network, including not only internal hormones and protein kinases but also external light and other stimuli. Our findings provide new insights and the rich resource to unravel the genetic control of heading traits.